2001
DOI: 10.1016/s0969-2126(01)00679-7
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Phosphorylated GSK-3β Complexed with a Peptide, FRATtide, that Inhibits β-Catenin Phosphorylation

Abstract: The Axin binding site on GSK-3 presumably overlaps with that for FRATtide; its proximity to the active site explains how Axin may act as a scaffold protein promoting beta-catenin phosphorylation. Tyrosine 216 phosphorylation can induce an active conformation in the activation loop. Pre-phosphorylated substrate peptides can be modeled into the active site of the enzyme, with the P1 residue occupying a pocket partially formed by phosphotyrosine 216 and the P4 phosphoserine occupying the 'primed' binding site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
173
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(179 citation statements)
references
References 44 publications
4
173
0
2
Order By: Relevance
“…A short peptide (FRATtide) comprising amino-acids 188-226 from human FRAT1 is sufficient to inhibit GSK3 (Thomas et al, 1999;Bax et al, 2001). Mutation of the IKEA-box to IAQA has been shown to disrupt Gsk3b binding in Xenopus GBP (Yost et al, 1998) Frat2, but not Frat1, is expressed at sites of Frizzled/PCP-pathway activity Our in vitro experiments suggested a Gsk3b-independent activity that was more prominent for Frat2 than for (Figure 4).…”
Section: Ap-1 Activation By Frat2 Is Gsk3b Independentmentioning
confidence: 82%
“…A short peptide (FRATtide) comprising amino-acids 188-226 from human FRAT1 is sufficient to inhibit GSK3 (Thomas et al, 1999;Bax et al, 2001). Mutation of the IKEA-box to IAQA has been shown to disrupt Gsk3b binding in Xenopus GBP (Yost et al, 1998) Frat2, but not Frat1, is expressed at sites of Frizzled/PCP-pathway activity Our in vitro experiments suggested a Gsk3b-independent activity that was more prominent for Frat2 than for (Figure 4).…”
Section: Ap-1 Activation By Frat2 Is Gsk3b Independentmentioning
confidence: 82%
“…In addition to MAPKs, insertions in the kinase core between subdomains X and XI are found in the cyclin-dependent kinases and glycogen synthase kinase-3. Xray crystal structures of cyclin-dependent kinase 2 and glycogen synthase kinase-3 in complex with their regulatory factors have also recently demonstrated the functional importance of this region for these kinase families (33)(34)(35). Thus, the insertion in MAPKs and other structurally related serine/threonine kinases may act as a common docking site for a variety of regulatory proteins.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25] Recent studies revealed that intrinsic disorder is an abundant phenomenon and many proteins lack rigid 3-D structure under physiological conditions in vitro, existing instead as dynamic ensembles of interconverting structures. [26][27][28][29][30] In contrast to ordered proteins whose 3-D structures are relatively stable and whose Ramachandran angles vary slightly around their equilibrium positions with occasional cooperative conformational switches, intrinsically disordered proteins or regions exist as dynamic ensembles in which the atom positions and backbone Ramachandran angles vary significantly over time with no specific equilibrium values and typically undergo non-cooperative conformational changes. 23 Statistical analysis shows that amino acid sequences encoding for the disordered proteins or regions are significantly different from those characteristic for the ordered proteins on the basis of local amino acid composition, flexibility, hydropathy, charge, coordination number and several other factors.…”
Section: Introductionmentioning
confidence: 99%